THE ROLE OF CORRECTIVE FEEDBACK STRATEGIES AND LEARNER UPTAKE IN DEVELOPING COMMUNICATIVE COMPETENCE - Asem Kuandikova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study examines how corrective feedback influences learner uptake in English as a Foreign Language classrooms. Six types of corrective feedback are identified and discussed: explicit correction, recasts, clarification requests, metalinguistic feedback, elicitation, and repetition, alongside corresponding categories of learner uptake, ranging from successful repair to needs-repair. The analysis draws on foundational research in second language acquisition to explore how different feedback strategies vary in their effectiveness at prompting learner engagement and error correction. Particular attention is given to the role of learner motivation and individual variation in shaping feedback outcomes. The paper concludes by considering how corrective feedback can be integrated strategically into communicative classroom practice to support both linguistic accuracy and communicative competence, positioning feedback not as a source of anxiety but as a meaningful driver for language growth.